Credit crunches from occasionally binding bank borrowing constraints - Tom D. Holden; Paul Levine; Jonathan M. Swarbrick (Deutsche Bundesbank, 2018)
We present a model in which banks and other financial intermediaries face both occasionally binding borrowing constraints, and costs of equity issuance. Near the steady state, these intermediaries can raise equity finance at no cost through retained earnings. However, even moderately large shocks cause their borrowing constraints to bind, leading to contractions in credit offered to firms, and requiring the intermediaries to raise further funds by paying the cost to issue equity. This leads to the occasional sharp increases in interest spreads and the counter-cyclical, positively skewed equity issuance that are characteristic of the credit crunches observed in the data.
Keywords: E22; E32; E51; G2; 330; Occasionally binding constraints; Credit crunches; Financial crises; Spreads; Dividends; Equity; Banking